Influence of organic matter on fusarium disease incidence in 'Pérola' pineapple - Goes, Antonio de; Gadélha, Ricardo Sérgio de Sarmento; Vieira, Alcílio (Pesquisa Agropecuaria Brasileira, 2014)
The effect of three levels of organic matter on the incidence of Fusarium moniliforme var. subglutinans in ‘Pérola' pineapple slips, planted in Regosol soil under field conditions was tested. According to the results there was no statistical difference among organic matter levels and the control. The incidence of Fusarium moniliforme var. subglutinans detected was caused by the use of slips infected before the test was established.